Polyurethane foams obtained from castor oil-based polyol and filled with wood flour - Mosiewicki, Mirna Alejandra (2009)
A natural polyol was prepared from castor oil by alcoholysis with triethanolamine. The oil and the oil-based polyol were characterized by infrared spectroscopy and through the analytical determination of their functional groups, both techniques indicating that the hydroxyl content increased significantly after the alcoholysis reaction. The modified oil was subsequently used as the polyol component in the formulation of rigid polyurethane foams. Wood flour was chosen to be incorporated as filler in these materials. Physical, thermal, and mechanical properties of the neat and reinforced foams were measured, analyzed, and compared to a reference commercial system. The chemical reaction between wood flour and isocyanate strongly affected the composites response to thermo-gravimetric tests. Compression modulus and yield strength decreased as wood flour content increased. The effect of the foam density on the compression properties was also investigated.